East west interface of reality: A scientific and intuitive inquiry into the nature of reality - Augustine Pamplany; Job Kozhamthadam; PAMPLANY (Augustine); KOZHAMTHADAM (Job) (Pune Association of Science, 2003)
ASSR is and interdisciplinary association in Jnana Deepa Vidyapeeth, Pune, India for the promotion of healthy and fruitful dialgoue between science and region for the good of the society.
Keywords: Reality in Retrospect; Quantum Wrestling with Reality; New Vision of Reality; Reality in Cross Roads; Reality in Praxis